Հայ կինը ցեղասպանության և ինքնապաշտպանական հերոսամարտերի ընթացքում. դրվագներ - Սվազլյան, Վերժինե Գ. (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
During over 60 years, owing to my consistent quests in the various regions of Armenia, as well as during my short-term personal or scientific trips to Syria, Lebanon, Egypt, Greece, France, Canada, the USA and Turkey, I have constantly searched and discovered representatives of the eyewitness survivors of the Armenian Genocide, including women, who have recalled their direct impressions through memoir-testimonies and historical song-testimonies. Women, who were emotional and sensitive by nature, have borne on their scraggy shoulders the whole weight of the sufferings of the deportation, the exile and the massacre of the Armenians. Consequently, they have vividly described in detail the tragic and heroic events of the Armenian Genocide. На протяжении около 60 лет, благодаря кропотливым поискам как в различных районах Армении, так и в ходе краткосрочных личных поездок в Сирию, Ливан, Египет, Грецию, Францию, Канаду, США и Турцию, а также во время имевших место в этих странах научных конференций нам удалось найти свидетелей-очевидцев Геноцида, в том числе – женщин, которые передали свои непосредственные впечатления через свидетельств-воспоминания и песень исторического характера.
Keywords: Հայոց ցեղասպանություն